EYE INJURIES OF FORENSIC EXAMINATION: INVESTIGATION, ANALYSIS, EXPERT PERSPECTIVES - Ganieva Nilufar Khamroevna; Shamsutdinova Zamira Murot kizi (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Annotation: The article presents a forensic medical analysis of eye injuries, focusing on mechanisms, classification, and diagnostic methods. It examines trauma caused by blunt, sharp, firearm, and explosive agents, emphasizing the importance of detailed documentation and expert evaluation. Modern imaging and histological tools are discussed as key elements in forensic practice. The article offers practical insights for forensic experts through case studies and current methodologies.